Biodegradable chitosan-glycolipid hybrid nanogels: A novel approach to encapsulate fucoxanthin for improved stability and bioavailability. (January 2015) - Ravi, Hindupur; Baskaran, Vallikannan
Abstract: This study aimed to improve the stability and biological availability of carotenoid fucoxanthin (FUCO) encapsulated in chitosan (CS) – sodium tripolyphosphate (TPP) – glycolipid (GL) nanogels, prepared by ionic gelation method. Scanning Electron Microscopic analysis and Dynamic Light Scattering examination revealed smooth and spherical nanogels with size range of 200–550 nm in weight ratios of CS: TPP (2.5:1), CS: GL (1:0.5). The zeta potential values (+30 to +50 mV) indicate that CS-NGs with FUCO + GL were more stable than that of CS-NGs + FUCO with no GL (+15 mV). The Fourier Transform Infrared Spectroscopy (FTIR) showed an extensive hydrogen bonding interaction between the FUCO and CS. X-ray Diffraction revealed FUCO is distributed in a disordered (amorphous) state in CS-NGs. Encapsulation efficiency, loading capacity and the yield of CS-NGs with FUCO + GL were 90%, 47% and 70%, respectively which is, significantly higher, than that of CS-NGs + FUCO without GL. Stability studies illustrated that glycolipid offers enhanced FUCO stability ( t 1/2, 45 h) with CS-NGs compared to that of with no GL ( t 1/2, 15 h) and standard FUCO ( t 1/2, <5 h). The bioavailability of FUCO in vitro from CS-NGs with GL was higher (68%) compared to that of CS-NGs + FUCO without GL (51%), FUCO with GL (35.5%) and control (21.5%). In conclusion, the stability and bioavailability of FUCO was improved by nanoencapsulation of FUCO with CS + GL. Graphical abstract: Highlights: Scanning Electron Microscope revealed spherical nanogels with 200–550 nm in size. X-ray diffraction reveals FUCO is distributed in a disordered state in CS-NGs + GL. Glycolipid offers enhanced FUCO stability and encapsulation efficiency in CS-NGs. In vitro bioavailability of CS-NGs with FUCO + GL is higher compared to control.